Effects of phenol on metabolic activities and transcription profiles of cytochrome P450 enzymes in Chironomus kiinensis larvae. Issue 1 (23rd October 2015) - Cao, C.W.; Sun, L.L.; Niu, F.; Liu, P.; Chu, D.; Wang, Z.Y.
Abstract: Phenol, also known as carbolic acid or phenic acid, is a priority pollutant in aquatic ecosystems. The present study has investigated metabolic activities and transcription profiles of cytochrome P450 enzymes in Chironomus kiinensis under phenol stress. Exposure of C. kiinensis larvae to three sublethal doses of phenol (1, 10 and 100 µM) inhibited cytochrome P450 enzyme activity during the 96 h exposure period. The P450 activity measured after the 24 h exposure to phenol stress could be used to assess the level (low or high) of phenol contamination in the environment. To investigate the potential of cytochrome P450 genes as molecular biomarkers to monitor phenol contamination, the cDNA of ten CYP6 genes from the transcriptome of C. kiinensis were identified and sequenced. The open reading frames of the CYP6 genes ranged from 1266 to 1587 bp, encoding deduced polypeptides composed of between 421 and 528 amino acids, with predicted molecular masses from 49.01 to 61.94 kDa and isoelectric points (PI) from 6.01 to 8.89. Among the CYP6 genes, the mRNA expression levels of the CYP6EW3, CYP6EV9, CYP6FV1 and CYP6FV2 genes significantly altered in response to phenol exposure; therefore, these genes could potentially serve as biomarkers in the environment. This study shows that P450 activity combined with one or multiple CYP6 genes could be used to monitor phenol pollution.